2015
DOI: 10.3233/rnn-140396
|View full text |Cite
|
Sign up to set email alerts
|

Delayed restraint procedure enhances cognitive recovery of spatial function after fimbria-fornix transection

Abstract: The improved task performance of lesioned animals suggests a therapeutic effect of this manipulation, independent of BDNF. This effect is sensitive to the temporal administration of treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
4
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 91 publications
1
4
0
Order By: Relevance
“…The present results parallel other results generated in our laboratory, showing a therapeutic effect of a delayed physical activation 21 days after brain injury, and a less beneficial effect of physical activation administered in the early posttraumatic period (Gram et al, 2015;Malá et al, 2012).…”
Section: Discussionsupporting
confidence: 93%
“…The present results parallel other results generated in our laboratory, showing a therapeutic effect of a delayed physical activation 21 days after brain injury, and a less beneficial effect of physical activation administered in the early posttraumatic period (Gram et al, 2015;Malá et al, 2012).…”
Section: Discussionsupporting
confidence: 93%
“…For example, both recognizing and understanding the distance to an object of interest, or understanding and recognizing obstacles as they are approached (see (Reiner, 2008) for additional potential benefits of such pairing). Furthermore, the EyeCane can potentially reveal points of interest users can zoom-in to with the EyeMusic’s zooming-in mechanism to perceive with higher resolution, thus better understanding their content (Buchs, Maidenbaum, Levy-Tzedek, & Amedi, 2015). This multisensory integration of approaches can be further implemented to a multimodal integrated visual rehabilitation setup (Maidenbaum, Abboud, & Amedi, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, neither the voluntary nor forced exercise regimens enhanced the posttraumatic task acquisition. It may be argued that exposure to forced exercise is a stressful event, however, as previously noted (see Greenwood et al 2013), stress per definition does not have to hinder the positive effects of exercise and may, under certain circumstances, even promote posttraumatic cognitive recovery (Gram et al 2015, Malá et al 2008. Several studies report a positive impact of post-injury exercise on spatial acquisition paradigms (Cechetti et al 2012, Griesbach et al 2004b, Kim et al 2010, Piao et al 2013, Shen et al 2013, Shih et al 2013, Sim et al 2004.…”
Section: Discussionmentioning
confidence: 92%
“…Cain et al 2006, de Bruin et al 2001, Gram et al 2015, Malá et al 2008, 2012, Mogensen et al 2004a. Interestingly, two studies that previously studied recovery of allocentric place learning have shown that the transection-induced deficit can be ameliorated either by applying a delayed (21-days) restraint procedure or a delayed (21-days) exercise regimen post-injury (Gram et al 2015(Gram et al , 2016. The applied lesion does, however, also disrupt a brain region involved in exercise-induced plastic reorganization processes, such as enhanced expression of synaptic molecules, increase in neurotrophic factors, and increased neurogenesis (Berchtold et al 2010, Farmer et al 2004, Griesbach et al 2004a, Kleim et al 2003, Vaynman et al 2003, Yau et al 2012.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation